Mechanistic insight into bimetallic CoNi-MOF arrays with enhanced performance for supercapacitors. Issue 9 (26th February 2020) - Chu, Xianyu; Meng, Fanling; Deng, Ting; Lu, Yue; Bondarchuk, Oleksandr; Sui, Manling; Feng, Ming; Li, Haibo; Zhang, Wei
Abstract : This work presents the architecture and mechanistic clarification of oriented bimetallic CoNi-MOF electrode materials for high-performance supercapacitors. Abstract : Engineering multicomponent electroactive materials is an effective strategy to improve electrochemical performance by adjusting the atomic and electronic structure. In this work, we directly synthesize oriented bimetallic CoNi-MOF nanosheets on CFP (carbon fiber paper). The CoNi-MOF/CFP shows high specific capacitance, outstanding rate capability and long-term cycling stability compared to a monometallic Ni-MOF or Co-MOF. By adjusting the Co/Ni molar ratio, CoNi23/CFP (Co : Ni = 2 : 3) displays the highest specific capacitance (2033 F g −1 at 1 A g −1 ). The introduction of Co into the Ni-MOF matrix shortens Co/Ni-centered bond distances, resulting in improved bond strength, facilitating the charge transfer and increasing the electrical conductivity of the CoNi-MOF, which were proved by X-ray absorption fine structure (XAFS) spectroscopy, high angle annular dark field (HAADF) imaging, and electrochemical impedance spectroscopy (EIS). Our study demonstrates the origin of performance improvements and, therefore, may provide a feasible scheme to unlock high-performance MOF electrode materials.